Targeting Co-Stimulatory Pathways in Gene Therapy - Yang, Yiping; Huang, Xiaopei (Frontiers in Microbiology, 2011)
Gene therapy with recombinant viral vectors such as adenovirus and adenovirus-associated virus holds great promise in treating a wide range of diseases because of the high efficiency with which the viruses transfer their genomes into host cells in vivo. However, the activation of the host immune responses remains a major hurdle to successful gene therapy. Studies in the past two decades have elucidated the important role co-stimulation plays in the activation of both T and B cells. This review summarizes our current understanding of T cell co-stimulatory pathways, and strategies targeting these co-stimulatory pathways in gene therapy applications as well as potential future directions.